Early-Stage Cannabis Regulatory Policy Planning Across Canada's Four Largest Provinces: A Descriptive Overview. (24th August 2019) - Watson, Tara Marie; Hyshka, Elaine; Bonato, Sarah; Rueda, Sergio
Abstract: Background : Observing and documenting major shifts in drug policy in a given jurisdiction offer important lessons for other settings worldwide. After nearly a century of prohibition of non-medical use and sale of cannabis, Canada federally legalized the drug in October 2018. Across this geographically large and diverse country, there is a patchwork of cannabis policies as the provinces and territories have developed their own regulatory frameworks. Objectives : As drug policy transitions are often studied well after implementation, we document early stage cannabis regulatory policy planning in the four most populous provinces of Québec, Ontario, Alberta, and British Columbia. Methods : In June 2018, we systematically searched peer-reviewed and gray literature (such as web content, reports, and policy documents authored by varied authorities and organizations) to identify key aspects of the evolving provincial cannabis legalization frameworks. In the absence of peer-reviewed studies, we reviewed primarily gray literature. Results : For each of the four provinces examined, we provide a succinct overview of early-stage public consultation, plans for cannabis distribution and retail, other key regulatory features, endorsements of a public health approach to legalization, general alignment with alcohol policy, and contentious or standout issues. Conclusions/Importance : Our review clearly illustrates that cannabis legalization in Canada is not unfolding as monolithic policy, despite a federal framework, but with divergent approaches. The public health outcomes that will result from the different provincial/territorial regulatory systems remain to be measured and will be closely monitored.